RESPONS FUNGSIONAL BURUNG PENTET (Lanius sp.) TERHADAP BELALANG KEMBARA (Locusta migratoria manilensis) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT Thefunctional response of predatory bird, Lanius sp. (Passeriformes: Laniidae) on migratory locust [Locusta migratoria manilensis (Orthoptera: Acrididae)] had been studied under restricted condition. The migratory locusts were reared in the green house. Second and fourth nymph instars along with adult stages of the migratory locust were used in this trial. Maximum feeding and functional response of the predatory bird against the migratory locust were determined. Research protocol used follows Holling s model. Results showed that the maximum feeding of the predatory bird was very high i.e. against 2nd and 4th instars and adult of the locust were 2.75 preys/minute, 0.13 preys/minute, and 0.09 preys/minute